2011
DOI: 10.1002/jca.20285
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐apheresis improves microcirculation of the upper limbs

Abstract: Lipid-apheresis (LA) is thought to improve microcirculation. However, limited data are available on the effects on peripheral microcirculation. We investigated upper limb microcirculation of 22 patients undergoing regular LA on a weekly basis before and after LA. Using standardized semiquantitative scales, we analyzed blood flow, vasomotor function, and erythrocyte aggregation by capillary microscopy. In addition, capillary blood flow in quiescence and under heat and cryo-stress was evaluated by photoplethysmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
(44 reference statements)
3
4
0
Order By: Relevance
“…Many diseases such as hypercholesterolemia, hypertension, diabetes, cardiovascular disease, and insulin resistance have been noted to be correlated with increased levels of ADMA. Our results were in line with those found by Rossenbach et al, who reported a decrease in ADMA levels (-74.1±23%) via LDL-apheresis (15) . We found significantly lower ADMA levels in post-LDLapheresis homozygous patients when compared with heterozygous hyperlipidemic patients and healthy subjects.…”
Section: Discussionsupporting
confidence: 94%
“…Many diseases such as hypercholesterolemia, hypertension, diabetes, cardiovascular disease, and insulin resistance have been noted to be correlated with increased levels of ADMA. Our results were in line with those found by Rossenbach et al, who reported a decrease in ADMA levels (-74.1±23%) via LDL-apheresis (15) . We found significantly lower ADMA levels in post-LDLapheresis homozygous patients when compared with heterozygous hyperlipidemic patients and healthy subjects.…”
Section: Discussionsupporting
confidence: 94%
“…In accordance to the already shown and here also observed LA associated decrease of ADMA serum level by approximately 70%, for ADMA the mean plasma half-life is suggested to be 15 min, but is certainly longer in the present cohort suffering from hypercholesterolemia by which ADMA degradation is strongly impaired [12,29]. The previously determined serum half-lifes of the investigated biomarkers are even longer and therefore contribute to the plausibility of the LA induced reduction in the current study (CRP 19h, PAPP-A 53h, VCAM 4h, MMP-9 7-150h) [30][31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…ADMA is suggested to play a pivotal role in plaque destabilization and is considered as a cardiovascular risk factor [21]. In the current study there was a reduction of 69.7 6 18.4% (P < 0.01), with the highest value in DALI (88.6 6 1.6%), followed by DFPP (68.6 6 17.3%) and HELP (52.56 6 10.18%) (Data already shown in Rossenbach et al [12]) whereby reduction rates in DALI-treated patients differed significantly from those treated with DFPP (P 5 0.002) or HELP (P 5 0.0039). Intergroup comparison made no significant difference between group A before LA, group B and C, whereas EP ADMA-levels were significant lower compared with the control groups (P < 0.01) (Fig.…”
Section: Lipoprotein Apheresis Reduced Svcam-1 Mmp-9 and Admasupporting
confidence: 78%
“…Another group showed an improvement in the micro circulation of the upper limbs under lipoprotein apheresis [49]. After lipoprotein apheresis sessions, the parasympathetic response to cardiovascular stimulation improved and sympathetic outflow to peripheral vasculature was reduced [50].…”
Section: Experience With Lipoprotein Apheresis N Effects On Lipid Conmentioning
confidence: 99%